Gambaran Intensitas Nyeri pada Pasien Post Operasi Sectio Caesarea dengan Metode Enhanced Recovery After Surgery (ERAS) di Rumah Sakit Islam Fatimah Cilacap - Nur Mutmainah; Tophan Heri Wibowo; Septian Mixrova Sebayang (CV. ALIM'SPUBLISHING, 2026)
Postoperative pain following Sectio Caesarea (SC) is a common clinical problem, reported within the first 24 hours in approximately 50-85% of patients. This postoperative pain can affect maternal comfort, early mobilization, and the recovery process. Theoretically, post-SC pain is associated with tissue trauma and nociceptive responses. Enhanced Recovery After Surgery (ERAS) is an increasingly implemented method because it is considered capable of accelerating postoperative recovery and reducing pain intensity after surgical procedures. This study aimed to describe the distribution of post-Sectio Caesarea pain intensity based on patient characteristics. This research employed a descriptive quantitative design with an observational approach. Data were collected using a total sampling technique from all post-SC patients managed with the ERAS method at RSI Fatimah over a one-month period, with a total of 50 respondents. The research instrument used was the Visual Analogue Scale (VAS). Data were analyzed univariately in the form of frequency and percentage distributions. The results showed that the majority of respondents were in early adulthood (26-35 years), accounting for 40 respondents (80.0%), multiparous women totaled 30 respondents (60.0%), maternal indications were found in 33 respondents (66.0%), and 27 respondents (54.0%) had no previous history of SC. Within the first 2 hours after SC, most mothers experienced mild pain (scale 1-3), totaling 31 respondents (62.0%). At 8 hours after analgesic administration, mild pain remained predominant, with 36 respondents (72.0%). In conclusion, most mothers who underwent Sectio Caesarea using the ERAS method experienced mild pain during the early postoperative period.